Synergistic effects of nelfinavir and bortezomib on proteotoxic death of NSCLC and multiple myeloma cells - Kawabata, S (Nature Publishing Group, 2012)
Exploiting protein homeostasis is a new therapeutic approach in cancer. Nelfinavir (NFV) is an HIV protease inhibitor that induces endoplasmic reticulum (ER) stress in cancer cells. Under conditions of ER stress, misfolded proteins are transported from the ER back to the cytosol for subsequent degradation by the ubiquitin–proteasome system. Bortezomib (BZ) is a proteasome inhibitor and interferes with degradation of misfolded proteins. Here, we show that NFV and BZ enhance proteotoxicity in non-small cell lung cancer (NSCLC) and multiple myeloma (MM) cells. The combination synergistically inhibited cell proliferation and induced cell death. Activating transcription factor (ATF)3 and CCAAT-enhancer binding protein homologous protein (CHOP), markers of ER stress, were rapidly increased, and their siRNA-mediated knockdown inhibited cell death. Knockdown of double-stranded RNA activated protein kinase-like ER kinase, a signal transducer in ER stress, significantly decreased apoptosis. Pretreatment with the protein synthesis inhibitor, cycloheximide, decreased levels of ubiquitinated proteins, ATF3, CHOP, and the overall total cell death, suggesting that inhibition of protein synthesis increases cell survival by relieving proteotoxic stress. The NFV/BZ combination inhibited the growth of NSCLC xenografts, which correlated with the induction of markers of ER stress and apoptosis. Collectively, these data show that NFV and BZ enhance proteotoxicity in NSCLC and MM cells, and suggest that this combination could tip the precarious balance of protein homeostasis in cancer cells for therapeutic gain.